2015
DOI: 10.1051/0004-6361/201424808
|View full text |Cite
|
Sign up to set email alerts
|

MUSE discovers perpendicular arcs in the inner filament of Centaurus A

Abstract: Context. Evidence of active galactic nuclei (AGN) interaction with the intergalactic medium is observed in some galaxies and many cool core clusters. Radio jets are suspected to dig large cavities into the surrounding gas. In most cases, very large optical filaments (several kpc) are also seen all around the central galaxy. The origin of these filaments is still not understood. Star-forming regions are sometimes observed inside the filaments and are interpreted as evidence of positive feedback (AGN-triggered s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 30 publications
3
22
0
Order By: Relevance
“…It is worth noting that we find similarities with the results recently obtained (also using MUSE) for the inner filament of Cen A (Hamer et al 2015). Indeed, both the inner and the outer filaments contain a well-defined linear knotty plus a more diffuse structure that show different kinematics and line ratios.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It is worth noting that we find similarities with the results recently obtained (also using MUSE) for the inner filament of Cen A (Hamer et al 2015). Indeed, both the inner and the outer filaments contain a well-defined linear knotty plus a more diffuse structure that show different kinematics and line ratios.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, they can place important constraints on the main parameters of the models used to simulate these interactions. Signatures of jet-ISM interactions have also been found in the nearby AGN Centaurus A (Cen A, see Rejkuba et al 2002;Oosterloo & Morganti 2005;Hamer et al 2015;Santoro et al 2015). This led us to choose this galaxy as a target for a detailed study of the jet-ISM interaction phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Werner et al (2010) found Hα filaments in the immediate downstream area from the jet-termination shock front in M87. Crockett et al (2012) and Hamer et al (2014) found evidence for shock-induced shells around star-forming clumps. The locations of these shells along the optical filaments connecting the two radio jets in the Centaurus A galaxy is consistent with material being swept along the back flow of the jet and ionised through shocks.…”
Section: Cause For Enhanced Star Formation In the 'Sausage' Clustermentioning
confidence: 99%
“…Optical observations have been carried on both the inner and outer filaments with MUSE on the VLT during the science verification period on 25 June 2014 (Hamer et al 2015 for the inner filament, Santoro et al 2015b for the outer filament). Hamer et al (2015) made three pointings with a 3 dither and 90…”
Section: Filament Oxygen Abundances As Deduced From Muse Datamentioning
confidence: 99%